Design research: a strategy for preservation of identity and crafts tradition (2019)
This paper focuses on the theoretical and methodological elements that guided the development of the research project with artisan communities, entitled ¿How to preserve the richness of craftsmanship tradition in the province of Alto Ricaurte in the Department of Boyacá? The project aims to promote dynamic integration of knowledge of designers and craftsmen, through work experiences that sought motivate new generations to perpetuate the crafts, and promote the conservation of regional craft identity. This paper, first presents some theoretical considerations about the concepts of identity, culture, tradition and knowledge dialogue, related to designer-craftsman work. Second, related the theoretical concepts that endured the research action process, that board the project from building dialogues between actors, and where the main axis was the concerted participation.